RAPID IDENTIFICATION OF ETIOLOGICAL AGENTS OF RESPIRATORY TRACT INFECTIONS DURING THE COVID-19 PANDEMIC USING THE MULTIPLEX-PCR METHOD - Zornic, Sanja (Medicinski časopis, 2023)
Objective: Most respiratory infections have similar symptoms, so it is clinically difficult to determine their etiology. This study aimed to show the importance of molecular diagnostics in identifying the etiological agent of respiratory infections, especially during the coronavirus disease 2019 (COVID-19) pandemic. Methods: A total of 849 samples from patients hospitalized at the University Clinical Center Kragujevac (from January 1 to August 1, 2022) were examined using automated multiplex-polymerase chain reaction (PCR) tests. The BioFire-Respiratory Panel 2.1 (RP2.1 plus) test was used for 742 nasopharyngeal swabs [identification of 19 viruses (including SARS-CoV-2) and four bacteria] and for 107 tracheal aspirates, the BioFire-Pneumonia Panel was used [identification of 18 bacteria and nine viruses] (BioMérieux, Marcy l’Etoile, France). The tests performed according to the manufacturer’s instructions, and the results were available within an hour. Results: From 582 (78.4%) samples, the RP2.1 plus test identified at least one pathogen. The rhinovirus (20.6%), SARS-CoV-2 (17.7%), influenza A (17.5%), respiratory syncytial virus (12.4%), and parainfluenza 3 (10.1%) were the most common. Other viruses were found less frequently, and Bordetella parapertussis was detected in one sample. From 85 (79.4%) samples, the BioFire-Pneumonia Panel test identified at least one bacterium or virus. The most prevalent bacteria were Staphylococcus aureus (42.4%), Haemophilus influenzae (41.2%), Streptococcus pneumoniae (36.5%), Moraxella catarrhalis (22.3%), and Legionella pneumophila (2.4%). Among viruses, rhinovirus (36.5%), adenovirus (23.5%), influenza A (11.8%), and the genus Coronavirus (4.7%), were detected. Conclusion: Multiplex-PCR tests improved the implementation of therapeutic and epidemiological measures, preventing the spread of the COVID-19 infection and Legionnaires’ disease.